STRUKTUR KOMUNITAS SERANGGA PERMUKAAN TANAH PADA PERKEBUNAN KELAPA SAWIT DI DESA KEPENUHAN TENGAH KABUPATEN ROKAN HULU SEBAGAI RANCANGAN BUKU SAKU SMA KELAS X PADA MATERI EKOSISTEM - Indah Susilawati; Yuslim Fauziah; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the structure community of soil surface insect in palm oil plantation in the village of Kepenuhan Tengah Of Rokan Hulu Regency and to produce a design learning resources in the form of pocket books. The study was conducted at the oil palm plantation in the village of Kepenuhan Tengah Of Rokan Hulu Regency and at the Biology Education Laboratory of the Teaching and Education Faculty of the University of Riau in August 2019 to September 2019. This research uses survey method. The location was chosen based on purposive sampling by considering the age factor of oil palm plantations. The parameters in this research are diversity index (H'), dominance index (C), importance index (INP), species composition, supporting parameters include soil temperature, soil moisture, and soil pH. The results obtained by the structure of land surface insect communities was found to have a moderate the level of diversity in the range 1.51-2.25. The dominance index of soil surface insects is relatively low, ranging from 0.12 to 0.31. The highest importance index of the four stations was found at station IV, Anoplolepis gracilipes species with INP 61.21%. The composition of soil surface insects was found 5 orders, 10 families and 14 species with the highest proportion is Hymenoptera which is equal to 52.53%. The results of the study have been made as a source of learning biology in the form of a Class X high school pocketbook on Ecosystem Materials.Key Words: Composition Pocket Book, Soil Surface Insects, The Structure Community